Uvod v odnosno antropologijo jezika - Ošlaj, Borut (Ars et humanitas, 2025)
The study explores the possibilities of understanding language against the background of the specificity of human relations and their philosophical-anthropological assump-tions. In doing so, it draws on some philosophical-anthropological theories that have addressed the problem of language to a greater or lesser extent (Plessner, Cassirer, Jonas), it takes cultural anthropology into account and some of the findings of quan-tum physics. By relational anthropology is meant the philosophical anthropological understanding of man as a being of specific relations at all the key levels of his life. The following topics receive special attention: the phenomenon of naming, the difference between mythical and logical words and consciousness, the transition from one to the other and the implications for language and consciousness.
Keywords: eccentric-diaphoric consciousness; ekscentrično-diaforična zavest; filozofija; imenovanje; nominalization; odnosi; philosophy; relations; simbolne forme; symbolic forms